IMPLEMENTASI METODE PROMETHEE UNTUK PENILAIAN INDEKS KINERJA BERDASARKAN KOMPETENSI DOSEN - Sumiyatun (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
Lecturers are both professional educators and researchers whose main tasks are transforming, developing and spreading knowledge, technology, and arts through education, research, and community service. This research produces a decision support system that can be used to determine the competence of lecturers at a tertiary institution. The use of Promethee as a multi-criteria analysis method is very helpful in determining the ranking of lecturer competencies implemented. Pedagogic competencies, 2. Professional competencies, 3. Personality Competencies and 4. Social Competencies. This system provides conclusions which consist of management in determining the ranking of competent lecturers